1992
DOI: 10.1111/j.1475-1313.1992.tb00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Refractive plasticity of the developing chick eye

Abstract: We have developed a lightweight plastic goggle with rigid contact lens inserts that can be applied to the eyes of newly hatched chicks to explore the range and accuracy of the developmental mechanism that responds to retinal defocus. Convex and concave lenses of 5, 10, 15, 20 and +30D were applied to one eye on the day of hatching. The chick eye responds accurately to defocus between -10 and +I5D, although hyperopia develops more rapidly than myopia. Beyond this range there is first a levelling off of the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
129
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(142 citation statements)
references
References 23 publications
11
129
1
Order By: Relevance
“…23,24 The same occurs if one puts a positive lens over the eye in chicks and monkeys. 25,26 The range of lens powers compensated for is greater in chicks than in monkeys, although monkeys can also compensate for stronger lenses if the lens power is stepped up gradually. 25,27 Similar mechanism may also be active in humans, however this entails further research.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 The same occurs if one puts a positive lens over the eye in chicks and monkeys. 25,26 The range of lens powers compensated for is greater in chicks than in monkeys, although monkeys can also compensate for stronger lenses if the lens power is stepped up gradually. 25,27 Similar mechanism may also be active in humans, however this entails further research.…”
Section: Discussionmentioning
confidence: 99%
“…For induced differences between treated and untreated eyes for lenses between À10 D and þ18 D, 48,49 MOR and axial length have a linear dependence with a slope equal to the À26 D/mm, as predicted (Appendix, equation A2). Thus, length changes almost completely account for long-term experimental induction of MOR, 48,49 without considering changes in power.…”
Section: Dependence Of Mor On Oal and Powermentioning
confidence: 99%
“…9 Evidences from animal experiments indicated that an accommodative lag during prolonged near work lead to hyperopic defocus on the retina which might result in excessive growth of the eye and a myopic refractive error. 10,11 A cohort study in Australia showed that primary school students with incident myopia were more likely to spend significantly more time studying and reading, 12 and a cross-sectional study in Beijing also demonstrated that a higher prevalence of myopia in highschool students was associated with shorter near work distance. 7 However, there have also been some studies reporting a weak or absent association between heavier load of near work and the prevalence or incidence of myopia.…”
Section: Introductionmentioning
confidence: 99%